Diferentes inclusões de fitase em dietas de frangos de corte - Oliveira, Eduardo Miranda de (2016)
Two experiments were conducted at the Animal Sciences Department from University of Missouri to evaluate the inclusion of phytase levels in broilers diets from d 1 to 42 d. The experimental design in the first experiment was completely randomized with six treatments, five replicates and 20 birds per each pen. In the second experiment was utilized the completely randomized design with six treatments, five replicates and 24 birds per each pen. In the first and second experiment, the dietary treatments included were: positive control, negative control, levels of 500 PU/kg, 1,500 PU/kg, 4,500 PU/kg e 13,500 PU/kg diet. In the first experiment were reduced levels of Ca (0.165%), aP (0.15%), metabolizable energy (52 kcal/kg), lysine (0.017%), methionine + cysteine (0.039%), threonine (0.033%) and sodium (0.020%). In the second experiment were reduced Ca (0.165%), aP (0.15%), metabolizable energy (52 kcal/kg) levels. In both experiments the nutritional requirements were reduced to fit in the control diet. In the first experiment the phytase supplementation didn’t influence (P > 0.05) the body weight, the feed intake, the feed conversion in broilers. In the second experiment broilers fed with positive control diet had higher (P ≤ 0.05) body weight and feed intake compared to the negative control, however, were no statiscally differ broilers fed with phytase levels. In the first and second experiment the tibia ash percent increased (P ≤ 0.05) with the phytase supplementation being equivalent the positive control diet. In both experiment the phytase addition increased (P ≤ 0.05) the apparent ileal digestibility of phosphorus, however, did not influence (P > 0.05) the apparent ileal digestibility of calcium. In both trials the phytase supplementation reduced significantly the total phosphorus on the litter compared to positive positive control treatment, but didn’t influence (P > 0.05) the dry matter and didn’t affect the foot pad dermatitis lesions. Phytase levels also didn’t influence (P > 0.05) on carcass yield and compostion realized in the second trial. In the initial phase the use levels up to 1500 FTU/kg diet with nutritional reduction and energy in the diet improves growth, bone mineralization, apparent ileal digestibility of phosphorus, reduces the excreted phosphorus and does not affect the litter quality in broilers. Levels of 500 FTU/kg feed for growing and finishing phase can be used without adverse effects in poultry.